Sensorineural component in chronic suppurative otitis media (Bangladesh Journal of Otorhinolaryngology, 2010)
A cross sectional study was conducted at the Department of Otolaryngology and Head-Neck surgery, Dhaka Medical College Hospital, Dhaka during the period of July 2005 to June 2007 to determine whether chronic suppurative otitis media (CSOM) can cause sensorineural hearing loss (SNHL) and to note its degree and its relation to duration of disease. 130 patients with unilateral CSOM were included in the study age ranging from 11 to 50 years after exclusion of other possible causes of SNHL such as meningitis, head injury, previous ear surgery, and chronic noise exposure. The use of unilateral CSOM cases provided a contralateral ear to serve as a control thus excluded common variables, such as presbycusis, parenteral ototoxic medications, metabolic disorders, and the effect of sex or genetics. Bone conduction threshold elevation between diseased and control ear was considered as the indicator of inner ear damage. In this series, CSOM is seen to be associated with sensorineural hearing loss. The study showed a bone conduction threshold elevation from 4.1dB to 10.7dB across frequency ranges. Significant threshold elevation was observed in relation to the disease duration. The average bone conduction loss at 4 kHz was higher than the average at the speech frequency range. This study suggests that CSOM can cause significant bone conduction threshold elevation and it should be considered when managing this problem. Early detection and prompt treatment may limit this potential handicap. Key words: CSOM; Sensorineural hearing loss; Bone conduction DOI: 10.3329/bjo.v15i2.5060 Bangladesh J Otorhinolaryngol 2009; 15(2): 69-74